Self-organized shocks in the sedimentation of a granular gas - Almazan Torres, Lidia; Serero, Dan; Salueña, Clara; Pöschel, Thorsten (Physical Review E - Statistical, Nonlinear, and Soft Matter Physics, 2015)
A granular gas in gravity heated from below develops a certain stationary density profile. When the heating is switched off, the granular gas collapses. We investigate the process of sedimentation using computational hydrodynamics, based on the Jenkins-Richman theory, and find that the process is significantly more complex than generally acknowledged. In particular, during its evolution, the system passes several stages which reveal distinct spatial regions of inertial (supersonic) and diffusive (subsonic) dynamics. During the supersonic stages, characterized by Mach>1, the system develops supersonic shocks which are followed by a steep front of the hydrodynamic fields of temperature and density, traveling upward.
Keywords: granular gas